Message - Kaijian Hou, Prof. Dr. (Universal Journal of Pharmaceutical Research, 2018)
The developments of new pharmaceuticals and novel methods of prevention, diagnosis and treatment of diseases would not be possible without significant advancement in pharmaceutical science and technology. The Universal Journal of Pharmaceutical Research (UJPR) aims to cover the outstanding developments in basic and translational research, ensuring its scientific priority and significance in the field of pharmaceutical science and technology. The Journal functions on principles of scientific excellence, publication ethics, and rapid dissemination of cutting edge research and innovation. We invite you to submit your most exciting work to the UJPR and to serve as reviewers when invited to do so. Reviewer engagement is one of the most important components in the pioneering, expedited, and fair review process to which the journal is committed to. UJPR board members will ensure the highest quality of the manuscripts accepted for publication through rigorous double blind peer review process, provided by the editors and a panel of strictly chosen experts in the field. Furthermore, the open access will provide UJPR considerable advantages over conventional journals of pharmaceutical sciences with greater visibility and impact. In coming yrs, we will achieve our target to add some new things, new concepts, to the available literature. Different articles published by UJPR will be beneficial and assist many researchers for their work. I congratulate all editorial board members of for their eforts and wish for the great success of “Universal Journal of Pharmaceutical Research”. I am delighted to announce the publication of the inaugural issue of the International, peer reviewed, open access UJPR on the behalf of the Editorial board. We are foreseeing a great success of the Journal in near future.